PROFIL HASIL BELAJAR KONSEP ASAM BASA DAN GARAM MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA SISWA KELAS VII SMP NEGERI 15 AMBON - Napsin Palisoa; Healthy Kainama; Mendy F Picaulima (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2018)
The research has been done to know profile of students result of teaching in acid, base and salt concepts through a contextual teaching and learning (CTL) using the class VII students of SMP Negeri 15 Ambon as a sampel of searching. Profile of student learning results in acid-base concept and salt obtained by the test results to learn. Descriptive analist showed that the results obtained studying the cognitive aspects of 80.07%, 86.02% affective aspects, while the aspect psiycomotoryc 87.29% students are success to achieved the KKM. After following the learning process, the result of the acquisition value of the final test (post-test) showed that 80.16% of students have been able to achieve KKM. Of the students test data during the learning process the Final Value (NA) all students showed that 100% all students have reached the KKM. Based on the results obtained can be concluded that by using a contextual approach to teaching and learning (CTL) on the concept of base and acid salts can encourage students to be able find a relationship between the material learned to real life situations of students and increase student result of learning.